Championing Diversity, Equity, and Inclusion, Volume 2 Effective Strategies for Management Education - Holmes IV, Oscar (Palgrave Studies in Equity, Diversity, Inclusion, and Indigenization in Business, 2025)
XXV, 191 p. 11 illus., 9 illus. in color.